A hierarchically structured urchin-like anode derived from chestnut shells for microbial energy harvesting. (10th September 2016) - Chen, Shanshan; Tang, Jiahuan; Jing, Xianyue; Liu, Yi; Yuan, Yong; Zhou, Shungui
Abstract: Electrode materials that have rich carbon contents and high specific surface areas are crucial for high power generation in microbial fuel cells (MFCs). A novel low-cost carbonized chestnut shell electrode (CSE) is examined as the anode for MFCs. The prepared CSE possesses a hierarchically structured urchin shape not only at the macroscopic level but also at the microscopic level. Electrochemical and bioelectrochemical properties of thorny CSEs and thornless CSEs were evaluated by impedance spectroscopy and cyclic voltammetry techniques. CSEs can achieve power densities of 759 ± 38 mW m −2 and coulombic efficiencies of 75% ± 12%, which are comparable to those of traditional electrode materials. This superior performance would be primarily due to a larger surface area on the CSE resulting from the microscopic/macroscopic three-dimensional urchin-shaped structure which increased the attachment of microorganisms. This study introduces a promising method for solving the environmental issues caused by chestnut shell disposal and offer new possibilities for value-added applications for chestnut shells by preparing CSEs.